The Role of Temporary Differences of Book Value and Tax-Based Earnings To Explain Earnings Persistence - Annas Cahyadi (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to examine how temporary differencesof book value and taxes-based earnings explain earnings persistence.First, this study examines and showsthat temporary differences provide additionalinformation on earnings persistence.The study then examines twopotential causes of differencesofbook value and tax-based earnings, namelyearnings management and tax planning.This study concludes that firms suspectedof performing earnings management and having the differences inbook value and tax-based earnings, their earnings will be less persistent thanother firms. On the other hand, for firms suspected of performing taxplanning,their earnings will be more persistent. This study also examines themore dominant factor that causes differences of earnings forfirms in Indonesiaand found that the differences are more influenced by tax planningpractices rather than earnings management.